EXPERIMENTAL STUDY OF LA(OH)3 AND GD(OH)3 SOLUBILITIES (25 TO 150°C), AND LA-ACETATE COMPLEXING (25 TO 80°C) - Deberdt S.; Castet S.; Dandurand J.L.; Harrichoury J.C.; Louiset I. (My University, 1998)
The solubilities of pure synthetic La and Gd hydroxides were measured in aqueous solutions over a wide range of pH (5-9.5) and temperature (40-150°C). The regression of these data is used to determine the first dissociation constant (KS0*) of the minerals as a function of temperature. The logarithm of these constants is found to be linearly related to the reciprocal temperature, which allows their reliable extrapolation to 25°C. In the range of temperature and pH investigated, only the REE3+ ion (where REE denotes La or Gd) is present in solution, indicating that the first hydrolysis constants proposed by , which are generally admitted, are overestimated.The complexation of La with acetate ion (AcO-) was studied by both solubility and potentiometric measurements. Potentiometric titrations are interpreted in terms of the formation of two complexes: LaAcO2+ and La(AcO)2+, and are used to generate the corresponding stability constants in the temperature range 25-80°C. These data allow accurate description of the La(OH)3 solubility increase, evidenced in acetate-bearing solutions.
Keywords: RARE EARTH ELEMENTS; LANTHANUM; GADOLINIUM; HYDROLYSIS; LA-ACETATE COMPLEXES; SOLUBILITY; POTENTIOMETRY; THERMODYNAMIC PROPERTIES